A study of cardiological autonomic neuropathy in Type 2 Diabetes Mellitus with reference to QT interval for its diagnosis - Inapakolla, Lakshmi Priya; Kotla, Ramgopal Teja (International Journal of Research in Medical Sciences, 2019)
Background: Presence of cardiac autonomic neuropathy (CAN) is responsible for silent myocardial infarction and sudden death in diabetics. Hence recognizing cardiac dysautonomia early, which is asymptomatic will help to delay or arrest its progression. Methods: A cross-sectional study to evaluate the Prevalence of Cardiovascular Autonomic Neuropathy in Type 2 diabetes and correlate it with duration of Diabetes and to investigate the relationship between cardiac autonomic dysfunction and corrected QT interval. Results: In the study population, the prevalence of definite CAN was 8%, 24% and 58% in group A, B and C respectively. The prevalence of definite CAN increases with increase in duration of diabetes. P value <0.001 significant. Conclusions: A significant correlation is present between Cardiovascular autonomic dysfunction and QTc prolongation. QTc interval in the ECG can be used to diagnose Cardiovascular autonomic neuropathy with a reasonable sensitivity and specificity.